Poverty in Iraq, 2012-2014 - World Bank (World Bank, Washington, DC, 2016)
This note describes the methodology used for estimating trends in poverty rates for Iraq using the 2012 Iraq household socio-economic survey and the 2014 continuous household survey; and presents the finding. The 2014 survey was designed to provide comparable and more frequent estimates of poverty, but fieldwork was disrupted in the second half of 2014 due to a deteriorating security situation. The methodology described in this note implements adjustments to weights and re-estimates the poverty line to establish poverty trends between the first half of 2012 and the first half of 2014 for all 18 governorates of Iraq; between 2012 and 2014 for these 13 governorates. The first set of estimates show that the pace of poverty reduction in Iraq was accelerating until the first half of 2014, while the second and third set of estimates quantify the adverse impact of the 2014 crisis on welfare in 13 governorates of Iraq.